2017
DOI: 10.1111/ocr.12136
|View full text |Cite
|
Sign up to set email alerts
|

Phonetic analysis during treatment with rapid maxillary expander

Abstract: Rapid maxillary expansion causes a slight phonetic change in the acoustical parameters of both consonants and vowels. The two-arm Hyrax caused less speech impairment than the four-arm Hyrax during the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…According to systematic reviews published in recent years, scientific evidence on RPE is basically limited to the assessment of the effects of orthodontic expanders on hard and soft tissues of the stomatognathic system [22][23][24][25]. Researchers have not fully explored the impact of these interventions on the quality of life of individuals [11,14]. Orthodontic interventions should be not only efficacious in treating malocclusion, but they should also cause minimal pain and minimal impact on patients' quality of life [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to systematic reviews published in recent years, scientific evidence on RPE is basically limited to the assessment of the effects of orthodontic expanders on hard and soft tissues of the stomatognathic system [22][23][24][25]. Researchers have not fully explored the impact of these interventions on the quality of life of individuals [11,14]. Orthodontic interventions should be not only efficacious in treating malocclusion, but they should also cause minimal pain and minimal impact on patients' quality of life [26].…”
Section: Discussionmentioning
confidence: 99%
“…A comparative study introduced another tooth-borne expander; the two-arm Hyrax, with improvement of the dental anchorage including anterior extension of the arms bilaterally and contour of the palatal surfaces of the premolars [ 14 ]. It has been demonstrated that the two-arm Hyrax provokes less speech impairment than the four-arm Hyrax during RPE [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that rapid palatal expansion causes a slight phonetic change in the acoustical parameters of both consonants and vowels. During therapy, the two-arm Hyrax caused less speech impairment than the four-arm Hyrax [29]. Interestingly, on the other hand, Yurttadur, et al [30] in their controlled clinical study, found no statistically significant differences between the treatment and control groups among all voice parameters.…”
Section: Impact Of Rapid Palatal Expanders On Speech Sound Productionmentioning
confidence: 89%
“…In another study conducted by Biondi, et al [29] the authors examined possible changes in phonetics induced by rapid palatal expanders. Thirty-five patients (aged 7-14 years, mean 9.3 ± 2.3 years), scheduled for rapid palatal expansion, were divided into two groups: Banded two-arm Hyrax and banded four-arm Hyrax.…”
Section: Impact Of Rapid Palatal Expanders On Speech Sound Productionmentioning
confidence: 99%